Evaluasi Implementasi Aplikasi P-Care Dengan Menggunakan Metode Hot-Fit Di Puskesmas Kabupaten Jembrana - Kurniastuti, A.A. Ayu Komang Indah; Wirajaya, Made Karma Maha; Tunas, I Ketut (Indonesian of Health Information Management Journal (INOHIM), 2024)
AbstractEvaluation is one of the important aspects needed to determine the success of implementing a primary-care (P-Care) application. In the P-care application at the Jembrana District Health Center, several obstacles were found in its implementation, including frequent errors. The aim of this research is to evaluate the implementation of the P-Care application at the Jembrana District Health Center using the Hot-Fit method. This type of research is quantitative with a cross-sectional approach with data collection techniques through interviews with questionnaires. The population in this study were all officers who used the P-Care application in 10 Jembrana Regency Health Centers with a total of 55 respondents. The results of the analysis obtained a score on the Human component of 3.06, which shows that users are satisfied with the performance of the P-Care application. In the Organizational component, a score of 2.9 was obtained, which shows that the community health center has an organizational structure that is able to support the P-Care application. In the Technology component, a score of 2.96 was obtained, which means that the existing technology is able to support the implementation of the application, and in the Net Benefit component, a score of 2.8 was obtained, which shows that the application provides good benefits for the organization. The implementation of P-Care in community health centers has gone well. There needs to be regular training for officers using the P-Care application to find out developments in the performance of the P-Care application.Keyword: P-Care, HOT-Fit, primary health care AbstrakEvaluasi merupakan salah satu aspek penting yang diperlukan untuk menentukan keberhasilan implementasi suatu aplikasi primary-care (P-Care). Pada aplikasi P-care di Puskesmas Kabupaten Jembrana ditemukan beberapa kendala dalam penerapannya diantaranya sering mengalami error. Tujuan dari penelitian ini untuk mengevaluasi implementasi aplikasi P-Care di Puskesmas Kabupaten Jembrana dengan metode Hot-Fit. Jenis penelitian ini adalah kuantitatif dengan pendekatan cross-sectional dengan teknik pengumpulan data melalui wawancara dengan kuesioner. Populasi pada penelitian ini adalah seluruh petugas yang menggunakan aplikasi P-Care di 10 Puskesmas Kabupaten Jembrana dengan jumlah total responden sebanyak 55 orang. Hasil analisis diperoleh skor pada komponen Manusia adalah 3,06 yang menunjukkan bahwa pengguna merasa puas dengan kinerja aplikasi P-Care. Pada komponen Organisasi diperoleh skor 2,9 yang menunjukkan puskesmas memiliki struktur organisasi yang mampu menunjang aplikasi P-Care. Pada komponen Teknologi diperoleh skor 2,96 yang berarti teknologi yang ada mampu mendukung penerapan aplikasi tersebut dan komponen Net Benefit diperoleh skor 2,8 yang menunjukkan aplikasi memberikan manfaat yang baik bagi organisasi. Penerapan P-Care di puskesmas telah berjalan dengan baik. Perlu adanya pelatihan kepada petugas pengguna aplikasi P-Care secara berkala untuk mengetahui perkembangan kinerja aplikasi P-Care.Kata Kunci: P-Care, HOT FIT, puskesmas